Duração e Memória: Bergsonismo e o piano no concerto em lá maior para piano com acompanhamento de Orquestra de Octávio Meneleu de Campos - Costa, Dayse Dias Silva e (2011)
This research aimed at rescuing the Concerto in A major for the Piano with Orchestral Accompaniment by the Brazilian composer Octávio Meneleu de Campos, from the state of Pará, regarding pianistic practice and analysis. This concerto was composed in the most productive period of the musician’s career, between 1903 and 1904, in the city of Milan. The manuscript transcription, the analytical study of the piece as well as the study of the Concerto piano part were of utmost importance to the development of this paper. The ways through which this analysis was carried out were mainly based on Bergson’s philosophy of duration (1934) and on Seincman’s study of the musical tempo (2001). Some of the Amazon Belle Époque musical memory investigation results are shown throughout the Concerto in A major for the Piano with Orchestral Accompaniment, where the composer’s style, his aesthetical referential within the Brazilian musical scenario and also his relationship with the romantic period are verified.